Impact Of Insulin Containing Regimen Vs Triple Oral Hypoglycaemic Agent Therapy On Health-Related Quality Of Life, Economic, And Clinical Outcomes In Poorly Controlled Type 2 Diabetes Outpatients In Yogyakarta - Tri , Murti Andayani (2010)
Type 2 Diabetes Mellitus (DM) is a progressive disease, and blood glucose control finally will get poorer because the function of pancreatic beta cells will decrease. Monotherapy with oral antidiabetics will not be effective for long so it is followed by two to three oral antidiabetics as combination therapy, and finally, type 2 DM patients will need exogenous insulin therapy. This research compared the addition and switching of therapy to insulin with triple oral therapy measuring three outcome parameters, i.e., clinical, humanistic and economic outcomes.